2020
DOI: 10.11604/pamj.2020.36.43.21085
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in Ghana: a retrospective analysis of a tertiary hospital data

Abstract: Introduction Hepatocellular carcinoma (HCC) is a cancer of global public health concern because of its high incidence and mortality. The impact is greatest in areas with high prevalence of its major risk factors including chronic hepatitis B virus (HBV). HBV is endemic in Ghana but a comprehensive data on HCC is lacking. The aim of this study was to describe the clinical, laboratory and radiological features of HCC at the Korle Bu Teaching Hospital in Ghana. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“…The predominance of males lent support to previous findings [ 14 ]. Our results are in line with studies reported from countries in the region, such as Ghana [ 15 ] and Egypt [ 16 ], where male domination was reported. The male predominance demonstrated in these studies was explained by the higher susceptibility of males to environmental carcinogens and greater exposure to environmental risk factors compared to the female population [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…The predominance of males lent support to previous findings [ 14 ]. Our results are in line with studies reported from countries in the region, such as Ghana [ 15 ] and Egypt [ 16 ], where male domination was reported. The male predominance demonstrated in these studies was explained by the higher susceptibility of males to environmental carcinogens and greater exposure to environmental risk factors compared to the female population [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…HCC is a challenging condition in sub-Saharan Africa because of its silent course and discovery at the end stage in most patients, the lack of medical facilities or expertise among physicians in-hospital for the administration of an appropriated treatment if necessary. 3 , 16 , 17 , 25–27 Our study demonstrates that one month survival was 28% of patients with advanced HCC survived at 30 days. The establishment of a simple and practical tool for routine utilization could be a better approach in these conditions to predict the mortality in such particular patients and to take the appropriate measure for patient treatment or assistance.…”
Section: Discussionmentioning
confidence: 59%
“… 3 , 6 , 18 The diagnosis of HCC was suspected if a liver mass was found on an ultrasonography or computed tomography scan with contrast enhancement and ascertained in the presence of one of the following criteria: radiological finding of portal vein thrombosis, elevation of the alpha-fetoprotein >400 ng/mL, and malignant hepatic cells found in the fine-needle aspiration cytology or histological pattern of HCC on liver biopsy examination. 3 , 6 , 16 , 17 Patients with incomplete data for establishing the diagnosis of HCC and those with secondary liver cancer, liver abscess, and benign liver tumors or liver vascular diseases were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations